2010
DOI: 10.1002/rcm.4482
|View full text |Cite
|
Sign up to set email alerts
|

Determination of elemental compositions by gas chromatography/time‐of‐flight mass spectrometry using chemical and electron ionization

Abstract: Many metabolomic applications use gas chromatography/mass spectrometry (GC/MS) under standard 70 eV electron ionization (EI) parameters. However, the abundance of molecular ions is often extremely low, impeding the calculation of elemental compositions for the identification of unknown compounds. On changing the beam-steering voltage of the ion source, the relative abundances of molecular ions at 70 eV EI were increased up to ten-fold for alkanes, fatty acid methyl esters and trimethylsilylated metabolites, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…This type of ionization yields many highly reproducible fragments and rearrangement ions, making identification of known compounds straightforward, based on comparison to mass spectra and retention indices of authenticated standards that have been deposited in databases. However, the intact molecular ions are often absent from the mass spectra (84). An alternative ionization approach for GC-MS is chemical ionization, which is softer and thus more commonly yields a molecular ion peak (74).…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…This type of ionization yields many highly reproducible fragments and rearrangement ions, making identification of known compounds straightforward, based on comparison to mass spectra and retention indices of authenticated standards that have been deposited in databases. However, the intact molecular ions are often absent from the mass spectra (84). An alternative ionization approach for GC-MS is chemical ionization, which is softer and thus more commonly yields a molecular ion peak (74).…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…Decision tree (DT)–based prediction algorithm makes use of mass spectral fragmentation and retention index (RI) information to enable sensitive and precise detection of compound substructures. It has also been shown that higher intensities of molecular and total ions (≤10-fold) are achieved by modulating a beam-steering voltage of the ion source at 70 eV EI of GC-TOF (e.g., alkanes, fatty acid methyl esters, and trimethylsilylated metabolites) (49). In this application, the accurate masses and isotopic data allowed more precise calculations of elemental compositions and facilitated metabolite identification when combined with fragmentation patterns from EI data.…”
Section: Targeted and Global Metabolomicsmentioning
confidence: 99%
“…If the dynamic range is exceeded (e.g., in high analyte concentrations), the MA will dramatically decrease. This was described by Abate et al [60] acquiring data in dynamic range enhancement (DRE) mode to allow the accurate mass analysis of very abundant GC-MS peaks that would otherwise saturate the detector and become unusable for accurate mass analysis.…”
Section: Resolution and Mass Accuracymentioning
confidence: 99%